The influence of local officials’ promotion incentives on Public-Private Partnership project investment from a political-performance-driven perspective: Empirical evidence from China - Lisha Zhang; Mingyang Yue; Shasha Du; Rong Zheng; Tao Zhu; Boyuan Tang (PLoS ONE, 2026)
The investment in PPP projects in China is large but quite uneven. Based on the political economy theory, using data from the public‒private partnership (PPP) industry issued by local municipal authorities from 2014 to 2018 in China, this paper explains the phenomenon of uneven PPP investment from a politically performance-driven perspective. The study shows that local officials have a strong incentive to increase investment in PPP projects that have positive visual effects on performance appraisal. Driven by promotion incentive, PPP investment demonstrates a phenomenon of “emphasizing performance over livelihood” and “emphasizing aboveground over underground”. The correlation between promotion incentives for municipal party secretaries and the annual incremental investment amount in growth-based PPP categories has an inverted U-shaped curve. Furthermore, the age of mayors has a heterogeneous influence on PPP investment, with those under 52 years of age being more willing to increase investment in growth-based PPP categories, as well as growth-based-visible PPP categories. Our study explores the political reasons for project investment mismatch and reveals the negative effect of local officials’ promotion incentives, which provides empirical experience in China for other countries to explore the relationship between officials’ promotion incentives and project investment.